Design and Research of a New Seal Ring Bush Silent Chain - Fu Zhenming; Li Cunzhi; Wang Guibin (Jixie chuandong)
A new type of seal ring bush silent chain (Zhenming chain) is brought forward and developed for the problem of severe vibration and high noise in the process of the motorcycle roller chain transmission. The structural innovation, mathematical modeling process and meshing principle of the silent chain are explained, and the RecurDyn dynamic simulation models of the new seal ring bush silent chain and a roller chain are established, which generate the operating wave curve caused by the polygon effect in the meshing process. The new seal ring bush silent chain is verified by variable speed and variable load wear test, noise test and road driving test. The results show that the noise of the new seal ring bush silent chain is lower than that of the roller chain, and the wear elongation of the new seal ring bush silent chain is lower than the roller chain. At the same time, it is proved that the innovative design scheme of the new seal ring bush silent chain is scientific and feasible.